Respon Mahasiswa Terhadap Penggunaan Media Web Berbasis Model Pembelajaran SAVI Untuk Peningkatan Kemampuan Menulis Dongeng Pada Mahasiswa - Moudizka, Kevin Dewanda; Suyatno, Suyatno; Indarti, Titik (Jayapangus Press, 2024)
This research aims to analyze student responses to the use of web media based on the SAVI learning model to improve their ability to write fairy tales. The research was carried out at the Department of Indonesian Language and Literature, FBS Unesa, with the research subjects being PBSI students class of 2022, Faculty of Languages and Arts (FBS) Surabaya State University for the 2023-2024 academic year. The object of research is student responses to the use of web media based on the SAVI learning model. The data collection technique uses a questionnaire method. The questionnaire consists of 12 questions which are divided into 2 indicators. These indicators include aspects of student acceptance regarding the ease of web media based on the SAVI learning model and web performance based on the SAVI learning model. From the calculations that have been carried out, the results obtained from the aspect of student acceptance regarding the ease of web media based on the SAVI learning model are 96% agreeing and 4% disagreeing. This shows that student acceptance regarding the convenience aspect of web media based on the SAVI learning model is in the very good category for use based on access, implementation and availability of devices by students in using web media based on the SAVI learning model. Meanwhile, regarding the performance aspect of web media based on the SAVI learning model, the average student answered agreeing at 92% and disagreeing at 8%. This shows that the appearance, way of working, and facilities provided by web media based on the SAVI learning model are very well received by students as users. These results show that learning to write fairy tales using web media based on the SAVI learning model received a very good response from students.